2021
DOI: 10.1177/2325967121989675
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Correction of Sports-Related Femoroacetabular Impingement in Competitive Athletes: 2-Year Clinical Outcome and Predictors for Achieving Minimal Clinically Important Difference

Abstract: Background: A growing body of literature supports surgical intervention for femoroacetabular impingement (FAI) in young, active athletes. However, factors likely to influence results in this cohort are less clearly defined. Purpose: To quantify changes in validated patient-reported outcome measures (PROMs) and determine whether differences in baseline athlete demographic characteristics, intraoperative findings, and surgical techniques are associated with achieving improved outcomes and minimal clinically impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In addition, an MCID based on a previously reported anchor-based reference scorespecifically, the percentage of possible improvement (POPI)-was included for the mHHS and SF-36, 6 as well as the UCLA and WOMAC. 23 The MCID, represented as a percentage change from baseline, has been shown to negate ceiling effects of PROMs and is independent of the baseline score. 6 For each case, the POPI achieved was calculated as follows: [PROM change / (maximum possible achievable score -preoperative score)] 3 100.…”
Section: Clinical Outcome Evaluationmentioning
confidence: 99%
“…In addition, an MCID based on a previously reported anchor-based reference scorespecifically, the percentage of possible improvement (POPI)-was included for the mHHS and SF-36, 6 as well as the UCLA and WOMAC. 23 The MCID, represented as a percentage change from baseline, has been shown to negate ceiling effects of PROMs and is independent of the baseline score. 6 For each case, the POPI achieved was calculated as follows: [PROM change / (maximum possible achievable score -preoperative score)] 3 100.…”
Section: Clinical Outcome Evaluationmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 Predictors of positive outcomes include younger age, male sex, body mass index less than 25, Tönnis grade 0, pain relief from preoperative intra-articular hip injections, and lower preoperative baseline patient-reported outcomes (PRO) scores. 9 , 10 …”
mentioning
confidence: 99%
“…Similarly, studies have identified predictors of negative outcomes, including symptom duration greater than 8 months, age greater than 45 years, chondral defects, decreased joint space greater than 2 mm, and increased lateral center edge angle. 8 , 9 , 10 While individual risk factors provide good information, these types of studies are limited by the fact that actual patient outcomes are not predicated on a singular risk factor but rather are complex and multifactorial in nature. 2 …”
mentioning
confidence: 99%
“…Favorable outcomes have been reported regarding the surgical treatment of FAIS, 12 , 25 , 27 , 39 , 43 not only regarding pain and function scores, but also regarding the rate of return to sport, including professional athletes. 8 , 28 , 32 , 42 The majority of these studies concern populations in Western countries, and outcomes in the Asian population have been limited to small sample sizes. 13 , 16 , 27 Moon et al 27 reported good outcomes in 73 patients with concomitant labral tears in Korea.…”
mentioning
confidence: 99%